Teologia do domínio: a influência religiosa e o perigo da imagem do caos = Dominion theology: the religious influence and the danger of the image of chaos = Teología del dominio: la influencia religiosa y el peligro de la imagen del caos - Xavier, Donizete José (Teocomunicação, 2024)
This article explores the concept of Dominion Theology, questioning whether it should be understood as a theological systematization or, more appropriately, as an ideological problematization. Given that it is not a single theology but rather a collection of multiple approaches, Dominion Theology presents itself as a complex phenomenon. The analysis highlights that this theology, in its various developments, has significantly contributed to the expansion of neo- -Pentecostal churches and the strengthening of Christian religious caucuses in Brazil, especially within the Legislative Branch. These groups, often defenders of an ultraconservative spectrum, use theological, moral, and eschatological arguments, frequently inspired by American thought. The article aims to demonstrate the background of this theology, emphasizing the imminent risk of power projection based on the construction of an image of chaos.